The α-casein gene polymorphism of goats in tropical environment - Mohammed, M.T.A.; Dhuha, J. M.; Haniza, M.Z.H.; Al-Bakri Salih, A. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study was completed to investigate the breed factor that influences milk production in different goat breeds in the tropical environmental area. A total of 28 goats were utilized in this work. These goats consisted of two different breeds, which were Anglo-Nubian and Saanen. Blood samples were withdrawn through jugular veinsof goats into plastic tubes without EDTA for gene polymorphism. A t-test was used to analyse if there are any significant differences in molecular weight and frequency values of DNA between breeds. Investigation of DNA polymorphism in alleles A, B and C of α-casein were identified in all breeds, while allele F were studied in Saanen goats only. As a conclusion; Saanen goats have more varieties α-casein allele